Transcranial magnetic stimulation reveals diminished homoeostatic metaplasticity in cognitively impaired adults. Issue 2 (27th November 2020) - Sundman, Mark H; Lim, Koeun; Ton That, Viet; Mizell, Jack-Morgan; Ugonna, Chidi; Rodriguez, Rudolph; Chen, Nan-Kuei; Fuglevand, Andrew J; Liu, Yilin; Wilson, Robert C; Fellous, Jean-Marc; Rapcsak, Steven; et al.
Abstract: Homoeostatic metaplasticity is a neuroprotective physiological feature that counterbalances Hebbian forms of plasticity to prevent network destabilization and hyperexcitability. Recent animal models highlight dysfunctional homoeostatic metaplasticity in the pathogenesis of Alzheimer's disease. However, the association between homoeostatic metaplasticity and cognitive status has not been systematically characterized in either demented or non-demented human populations, and the potential value of homoeostatic metaplasticity as an early biomarker of cognitive impairment has not been explored in humans. Here, we report that, through pre-conditioning the synaptic activity prior to non-invasive brain stimulation, the association between homoeostatic metaplasticity and cognitive status could be established in a population of non-demented human subjects (older adults across cognitive spectrums; all within the non-demented range). All participants ( n = 40; age range, 65–74, 47.5% female) underwent a standardized neuropsychological battery, magnetic resonance imaging and a transcranial magnetic stimulation protocol. Specifically, we sampled motor-evoked potentials with an input/output curve immediately before and after repetitive transcranial magnetic stimulation to assess neural plasticity with two experimental paradigms: one with voluntary muscle contraction (i.e. modulated synaptic activity history) to deliberately introduce homoeostatic interference, and one without to serve as a control condition. From comparing neuroplastic responses across these experimental paradigms and across cohorts grouped by cognitive status, we found that (i) homoeostatic metaplasticity is diminished in our cohort of cognitively impaired older adults and (ii) this neuroprotective feature remains intact in cognitively normal participants. This novel finding suggests that (i) future studies should expand their scope beyond just Hebbian forms of plasticity that are traditionally assessed when using non-invasive brain stimulation to investigate cognitive ageing and (ii) the potential value of homoeostatic metaplasticity in serving as a biomarker for cognitive impairment should be further explored. Abstract : Neural plasticity was assessed in healthy older adults with TMS. Upon neuropsychological evaluation, participants were stratified using validated cutoffs for cognitive dysfunction. Sundman et al. observed divergent neural plasticity profiles, particularly when stimulation was preceded by synaptic pre-conditioning. This suggests that mechanisms of metaplasticity may be associated with cognitive decline. Graphical Abstract: